BACTERIAL LYSATES IN COMPLEX TREATMENT OF RESPIRATORY INFECTIONS IN FREQUENTLY SICK CHILDREN - I.N. Lupan; L.A. Dulkin; I.M. Shepeleva ("Paediatrician" Publishers LLC, 2011)
The literature review analyzes the results of Imudon administration in pediatrics. The drug contains a mixture of purified lyzates of bacteria which are the most frequent causative agents of pathologic processes in oral cavity and throat. Presented data show high efficacy and safety of a drug. Key words: frequently sick children, respiratory infections, topical immunocorrector, clinical studies. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (4): 41-46)